Reflections on monitoring and evaluating climate adaptation - Nowak, Andreea C.; Rosenstock, Todd S. (Accelerating Impacts of CGIAR Climate Research for Africa, 2021)
Learning session on climate change adaptation metrics for smallholder agriculture, organized by BMGF and TNC